Moral Strategy - Feibleman, James K. author. aut Link
XII, 325 p. 1 illus.
Keywords: No statement, except one, can be made with which all philosophers would agree. The exception is this statement itself. The disagreement has the advantage that it gets all the proposals out into the open where they can be examined, but it has the dis advantage that the cogency of any one philosophy must rely entirely upon that wide public which is unprepared to deal with it. Fortunately, ethics has a more immediate appeal than some other branches of philosophy; yet the history of the topic gives no indication that this circumstance has had the happy results we might have expected. One peculiarity of ethics is that its problems are rarely settled on its own grounds. Ethical problems are for the most part referred to socially established moralities, and moralities are socially established not on the basis of philosophy but rather by some sponsoring insti or politics. Such establishments, however, tution, usually religion depend on the prior preparation of ethical proposals by philosophers. For it stands to reason that an ethics cannot be socially established if there is no ethics to establish. Thus philosophers provide the justifi cation for socially-established moralities while seeming not to do so.